Long-term follow-up of coronary angioplasty in patients with diabetes compared with nondiabetics - Brueren, B.R.G. (2004)
BACKGROUND: Some reports have indicated that in patients with diabetes mellitus and multivessel disease, coronary artery bypass surgery is preferred over percutaneous coronary intervention (PCI). We retrospectively compared outcome PCI in diabetic and nondiabetic patients. METHODS: Ninety-seven diabetics and 971 nondiabetics were included and randomised before PCI to aspirin alone or aspirin plus coumadin. Fifty diabetics and 481 nondiabetics underwent follow-up angiography. The primary endpoint comprised all-cause mortality, myocardial infarction or targetvessel revascularisation. RESULTS: Baseline characteristics were similar between the groups except for significantly more males and smokers among the nondiabetics. The diabetics had significantly more previous strokes, more left anterior descending coronary artery disease as well as more restenotic lesions and multivessel disease. At 30 days, the primary endpoint had occurred in five diabetics (5.2%) and 47 nondiabetics (4.9%), (p=0.8) and at one year in 17 (17.5%) and in 165 (17.1%), respectively (p=0.9). Event-free survival remained comparable during long-term follow-up (four years). Multivariate analysis showed no differences for the occurrence of any event (p=0.9, 95% CI 0.6-1.7). At six months, the minimal luminal diameter was significantly smaller in the diabetics (1.55±0.76 mm vs. 1.78±0.66 mm, p=0.01). Diabetics also had more restenosis (41% vs. 23%, p=0.003). CONCLUSION: Despite angiographical differences at six months between the diabetics and nondiabetics, both short-term and long-term clinical follow-up appeared to be similar.